Grow your global markets : a handbook for successful market entry - Hopkins, Raymond A. (Apress, 2017)
Use this comprehensive primer to simplify exporting, discover exportable products and services, and determine and select the best target market entry alternative while ensuring that you get paid. US small- to medium-size business owners (SMEs with less than 500 employees) interested in entering foreign markets will learn how to overcome the most significant challenges and barriers to entering foreign markets. Firms operate in a worldwide economy responsible today for 40 million US trade-dependent jobs and approximately six million US factory jobs--roughly half of all manufacturing employment, whether or not they have any interest in global business activities. In the face of globalization, small businesses must evaluate their strengths, weaknesses, opportunities, and threats and then develop strategies that effectively respond to the globalized business environment in which they operate. If your firm is growth-oriented--and what business is not?--you should grow global markets as an important strategic option allowing you to: Reach new customers/markets with little or no competition Reduce dependence on a limited number of major customers Even out business cycle-related demand fluctuations Extend the life of niche products to new markets Develop a global network of contacts and partners that improves their offerings to established customers What You'll Learn: Determine your role in global markets Identify target markets and find customers Negotiate around the world Complete the transaction and understand international trade procedures and regulations Understand the keys to global market growth Follow sample forms and sales proposals.